FEATURES OF TRADITION AND MODERNIZATION IN THE CONSTRUCTION OF A MODERN SOCIETY (Academicia Globe: Inderscience Research, 2022)
The article provides a comprehensive scientific review of the relationship between traditional and modern processes that play an important role in the development of any society, as well as the impact of these processes on socio-political institutions, as well as a number of suggestions and recommendations.